1997
DOI: 10.1111/1468-5949.00058
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Drawing in Graphic Design and the Implications for Curriculum Planning

Abstract: Over a number of years a programme of research has been carried out into the role of drawing in design processes, primarily the graphic design process, and on the possible implications for curriculum planing for design students. From the findings of an original in-depth analysis of the use of drawing in the commercial environment of the design consultant, various initiatives in educational planning and assessment in England and Scotland have been fostered and a contribution has been made to the ongoing debate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Novice 3 worked on two design drafts simultaneously, seemingly to his advantage: he mentioned that it helped him greatly in exploring visual elements. He extended what Schenk () has defined as the main creative phase into the production phase, not only by sketching ideas by hand but also by working with a computer on more than one draft simultaneously as a means of visual exploration. He commented that working on only one draft tended to force him to ‘sink into’ it and interfered with his ability to objectively evaluate its visual qualities.…”
Section: Evaluation Of the Methodologymentioning
confidence: 99%
“…Novice 3 worked on two design drafts simultaneously, seemingly to his advantage: he mentioned that it helped him greatly in exploring visual elements. He extended what Schenk () has defined as the main creative phase into the production phase, not only by sketching ideas by hand but also by working with a computer on more than one draft simultaneously as a means of visual exploration. He commented that working on only one draft tended to force him to ‘sink into’ it and interfered with his ability to objectively evaluate its visual qualities.…”
Section: Evaluation Of the Methodologymentioning
confidence: 99%
“…Addressing graphic design practice in particular, Schenk (1991;1997;2005) compared novice graphic designers' use of traditional and digital design tools, concluding that working with pen and paper enabled designers to generate more ideas than when working with digital tools. Schenk's studies of graphic designers' tool use during problem solving also found that sketching and drawing played a major part in graphic designers' processes.…”
Section: Design Practicementioning
confidence: 99%
“…Pam Schenk has produced a considerable body of analysis of sketching in the graphic design process [7], [8]. Her work describes the function-ality of sketching in design phases such as 'accepting briefing from the client' and 'passing on the briefing'.…”
Section: Research Practice and Educationmentioning
confidence: 99%